The Awareness of Oral Health Professionals regarding Medication-Related Osteonecrosis of the Jaws- a Descriptive Study - Alden Schnyder Jason D; N.K. Aditya; Uthra K S; Divya Parimi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objectives: This study aimed to evaluate and assess the knowledge of dental students and residents(postgraduate) about Medication-related Osteonecrosis of the jaw (MRONJ) to aid in future training and accommodate teaching programs that emphasize the topic's importance in dentistry. Materials and Methods: A self-administered questionnaire was sent to general dentists, residents and specialist dentists. It was divided into two sections: the first section was about general information such as participant designation, the participant's specialization, and the years of experience. The second section included questions about bisphosphonates (BPs) and their use and implications in dental practice. Descriptive statistics were derived, and the results were recorded. Result: 140 participants completed the questionnaire. 78.6% of respondents were aware of MRONJ, with a majority (35.7%) claiming to have some knowledge about the condition. Only 15% of the respondents had heard about the MRONJ guidelines issued by the AAOMS. Only 48 subjects (34.3%) could answer the six case-based scenario questions. 37.1% were confident in treating a patient with MRONJ symptoms, most of whom were post-graduate residents (48.8%). Conclusion: Although a convincing number of general dentists had answered case-based scenario questions correctly, and the majority of respondents with experience of less than three years had most correct answers, it was significant to note that most respondents were neither aware of AAOMS guidelines nor had confidence in treating or formulating a treatment plan for patients with MRONJ. The continued efforts toward planned teaching and learning programs will help the Oral health professionals be confident in examining and treating patients with MRONJ.